2022
DOI: 10.21037/atm-22-5067
|View full text |Cite
|
Sign up to set email alerts
|

Tissue factor as a new target for tumor therapy—killing two birds with one stone: a narrative review

Abstract: Background and Objective: Cancer is an important disease and can occur anywhere in the body. It is caused by uncontrolled cell growth that spreads to other body parts. This study extensively investigated the transmembrane receptor tissue factor (TF), which is the key motivator of the clotting cascade and plays an essential role in cancer-associated coagulation. TF is considered to be aberrantly expressed in various tumors and appears to promote tumor angiogenesis and metastasis. Therefore, this study was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 98 publications
(169 reference statements)
0
4
0
Order By: Relevance
“…One study has reported higher TF expression in glioblastoma in tumor biopsies obtained from patients [ 54 ]. It is now well-known that tissue factor, aside from its function as a procoagulant activator, plays a significant role in various tumor-associated mechanisms, including angiogenesis [ 55 ] and also it is suggested that, therapeutics that specifically target transcription factors may have wide clinical applications in tumor treatment [ 56 ]. These proteins can be evaluated as efficient anticancer target for other solid cancers.…”
Section: Discussionmentioning
confidence: 99%
“…One study has reported higher TF expression in glioblastoma in tumor biopsies obtained from patients [ 54 ]. It is now well-known that tissue factor, aside from its function as a procoagulant activator, plays a significant role in various tumor-associated mechanisms, including angiogenesis [ 55 ] and also it is suggested that, therapeutics that specifically target transcription factors may have wide clinical applications in tumor treatment [ 56 ]. These proteins can be evaluated as efficient anticancer target for other solid cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of blood clots can provide a physical scaffold for the migration of cancer cells and facilitate their spread to distant organs. Coagulation factors such as fibrin may promote cancer cell survival and protect them from immune surveillance [ 68 , 244 , 245 , 246 ].…”
Section: The Role Of the Coagulation System In Selected Disorders Of ...mentioning
confidence: 99%
“…Tisotumab vedotin is an ADC directed against tissue factor, with a cleavable linker and DM4 payload [ 79 ]. Tissue factor is physiologically expressed on adventitial cells and released after endothelial injury; however, it is also pathologically over-expressed on the surface of tumour cells and endothelial cells in various cancers, including pancreatic cancer, cervical cancer, sarcoma, lung cancer, triple-negative breast cancer, and acute lymphocytic leukaemia [ 100 ]. A phase II single-arm trial of tisotumab vedotin in patients with disease progression on or after doublet chemotherapy with bevacizumab demonstrated an ORR of 24%, median PFS of 4.2 months, and median overall survival of 12.1 months [ 79 ].…”
Section: Seminal Phase Ii/iii Trials Of Antibody–drug Conjugates In C...mentioning
confidence: 99%